"FAITH IS MORE IMPORTANT THAN BELIEFS AND RELIGIOS": COMPREHENSIONS OF NON-RELIGIOUS UNIVERSITY STUDENTS - Antonio Mezzomo, Frank; De Oliveira Pátaro, Cristina; de Fátima Grigoletto Bonini, Lara (LINKSCIENCEPLACE, 2026)
The study discusses the religious representations of young people who declare to believe in God, but do not participate in religion. The research includes 150 youth students from the State University of Paraná – Unespar. In order to identify the actions and understandings of university students, survey was conducted through an online platform. The results show that the students have beliefs and value the subjective dimension of the faith, based on private bricolages, and they experience the contemporary dynamics in the search for their autonomy. Discussion shows the distance of religious institutions, but the maintenance of their religiosities and beliefs. The research identificated subjective aspects of the religious field that influence in the identity and life of the non-religious youth of Unespar.